Infectious disease, the climate, and the future - Tong, Shilu (Environ Epidemiol, 2021)
Emergence and resurgence of infectious diseases are serious threats to population health. The ongoing COVID-19 pandemic has caused an enormous human toll and health crisis. Responses to the pandemic are significantly affecting the global economy. What is most concerning about COVID-19 is not the virus itself, but rather that it may compound with other and more serious crises. Climate change will likely affect human health, economy, and the society more than disease outbreaks. Governments at all levels, from local to international, can chart a greener, healthier, and equitable course for the future, investing in strategies and technologies that minimize and prevent risks, including those posed by climate change and the pandemic, promoting obligations to drastically reduce emissions, enhancing societal equality, improving community resilience, and achieving sustainable development goals.